2013
DOI: 10.1001/jamaoto.2013.4072
|View full text |Cite
|
Sign up to set email alerts
|

Depression Among Long-term Survivors of Head and Neck Cancer Treated With Radiation Therapy

Abstract: Despite a relatively high rate of depression among patients with head and neck cancer in the post-RT setting, mental health services are severely underutilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 17 publications
0
75
0
Order By: Relevance
“…Severe dysphagia resulting in gastrostomy dependence is a late effect of treatment that may develop or progress years after treatment, and once present, the majority of patients with severe dysphagia remain gastrostomy‐dependent despite aggressive therapeutic interventions . Prolonged NPO status has been shown to be associated with worse long‐term swallowing outcomes and depression . Prophylactic gastrostomy placement before or during treatment to prevent weight loss and provide a route for enteral feeding is commonly advised, but a growing body of literature suggests that prophylactic gastrostomy placement is associated with worse long‐term swallowing outcomes, and in fact may not prevent weight loss .…”
Section: Discussionmentioning
confidence: 99%
“…Severe dysphagia resulting in gastrostomy dependence is a late effect of treatment that may develop or progress years after treatment, and once present, the majority of patients with severe dysphagia remain gastrostomy‐dependent despite aggressive therapeutic interventions . Prolonged NPO status has been shown to be associated with worse long‐term swallowing outcomes and depression . Prophylactic gastrostomy placement before or during treatment to prevent weight loss and provide a route for enteral feeding is commonly advised, but a growing body of literature suggests that prophylactic gastrostomy placement is associated with worse long‐term swallowing outcomes, and in fact may not prevent weight loss .…”
Section: Discussionmentioning
confidence: 99%
“…59 When screening depression alone, the prevalence of these symptoms that are above cutpoints for depression range from 12% to 14%. 33,6066 A meta-analysis of major depression diagnosed with interviews in the non-palliative care setting found a prevalence of 16%. 67 This was confirmed in women with breast cancer who were followed 4 months after their diagnosis and over the course of 1 year were assessed a total of 7 times using a clinical interview and questionnaire.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…1,2 Previous work has shown that patients experience a wide continue. 24,25 Poor survival has been associated with anxiety, depression, and low health-related quality of life (HRQoL). 12 Screening for anxiety and depression in routine clinics 7,26 can give access to a variety of interventions, 27,28 and the head and neck Patients' Concerns Inventory (HNC-PCI) is a screening tool that is freely available.…”
Section: Introductionmentioning
confidence: 99%